Manufacturing strategies and choices in cultural contexts - Alas, Ruth; Kraus, Ants; Niglas, Katrin (Journal of Business Economics and Management, 2009)
Although any firm operates in a local environment, which includes specific economic, social and cultural contexts, there is still a lack of studies connecting culture and values with operations strategies and practices. This paper attempts to explore a look at how cultural dimensions are connected with manufacturing strategies and choices. The current article is based on data from the International Manufacturing Strategy Survey (IMSS) project and the GLOBE study. Advanced mass production is more common to countries with high assertiveness, power distance and uncertainty avoidance. The model of manufacturing strategies and choices in cultural context is developed based on empirical results of the study. First Publish Online: 14 Oct 2010